Critical behaviour of a polar-polar binary system from optical birefringence measurements. Issue 1 (2nd January 2016) - Sarkar, Sudipta Kumar; Chakraborty, Anish; Das, Malay Kumar
ABSTRACT: High resolution measurements of optical birefringence (Δ n ) have been carried out to study the critical behaviour at the nematic-isotropic (N–I) and smectic A-nematic (SmA–N) phase transitions in a binary system composed of nonyloxycyanobiphenyl (9OCB) and heptylcyanobiphenyl (7CB). From a fitting procedure compatible with the weakly first order nature of the N–I transition, the order parameter critical exponent β at the N–I transition has been found to be in well agreement with the tricritical hypothesis. The pretransitional behaviour at the SmA–N transition has been investigated with the aid of a differential parameter extracted from Δ n data and the yielded critical exponent α has been found to be non-universal in nature. A weak birefringence have been found to develop on approaching the N–I transition temperature, which is tentatively attributed to surface induced ordering. In this case, a treatment identical to that for the SmA–N transition yields a tricritical nature for the N–I transition in the investigated mixtures. Such an outcome has also appeared to be in well agreement with those obtained from the direct analysis of the Δ n data (i.e. in parameterisation of β ). Graphical Abstract: